Pengaruh Content Marketing, Influencer Marketing Dan Online Customer Review Di Tiktok Terhadap Keputusan Pembelian Brand Somethinc (Studi Kasus: Pada Generasi Z Di Surakarta) - Nadia Rahadewi Cahyaningtyas; Kusdiyanto Kusdiyanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of Content Marketing, Influencer Marketing, and Online Customer Reviews on TikTok on the purchasing decisions of the Somethinc brand among Generation Z in Surakarta. The research method used is quantitative with the Structural Equation Modeling (SEM) approach using SmartPLS 3. Data were collected through an online questionnaire with a purposive sampling technique, involving 100 respondents who had purchased Somethinc products. The results of the study show that Content Marketing has a positive and significant influence on purchasing decisions while Influencer Marketing and Online Customer Reviews do not have a significant influence on purchasing decisions. These findings confirm that content-based digital marketing strategies, influencer support, and customer reviews play an important role in shaping consumer purchasing decisions on TikTok. Therefore, companies are advised to optimize marketing strategies through educational content, real-life testimonials, and collaboration with influencers to increase consumer trust and buying interest..